Library online database system for undergraduate students - Azlan, Nor Athira; Mohammad Daud, Nur Hidayah; Zulkifli, Zahidah; Samsuri, Suhaila; Ali , Asma; Hussin, Husnayati (Asian Research Publishing Network (ARPN), 2015)
The demand of the good quality of research especially in academic field rose the emerging of library online databases services nowadays. Internet is the network of physical objects that enable the library online database services available. Most of the universities in Malaysia have subscribed the library online databases to provide students more opportunity to explore research resources not limited only in a certain region and country but throughout the world. The services are expected to give benefit to the postgraduate and undergraduate students for academic purposes. However, most of undergraduate students are not aware of the existence of library online databases services that universities provided. They also discouraged to use the services due to the difficulties they faced when they used the services. The purpose of this paper is to explore the factors influence undergraduate’s students use search engine for information searching, illustrate library online database systems and features in top research universities and make comparison with search engine, discuss current issues and problems and proposed library online database system that suitable with undergraduates’ students information searching preferences. Interviews and survey have been conducted at International Islamic University Malaysia, IIUM. There were 107 participants involved. As a result, current issues and problems are identified, list of library online database systems and it features are analyzed and the best library online database system and features are selected to be adapted for future development in International Islamic University Malaysia, IIUM library.